Pendampingan Peningkatan Ekonomi Kreatif Oleh-Oleh Khas Bekasi Bandeng Rorod dalam Upaya Mendukung Potensi Lokal di Bekasi Timur: Assistance in Increasing the Creative Economy of Bekasi Traditional Food Bandeng Rorod in Efforts to Support Local Potential in East Bekasi - Asri, Dyah Permata Budi; Sari, Athina Kartika; Saraswati, Henny (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Milkfish is one of the mainstays of fishery products for consumption in the Bekasi Regency, especially in Muara Gembong District, Bekasi Regency. In 2021 alone, the production of milkfish in Bekasi Regency reached 11,607 tons per year. With the large production of milkfish, many people have taken the opportunity to open culinary businesses, restaurants, and souvenirs made from milkfish. One of them is the Mpok Omah (Bandeng Rorod) culinary center, which has been running a Bandeng Rorod business since 2011, located at Perumnas 3, Jalan Maluku Raya Blok C1 No.3, East Bekasi. The purpose of this service was to provide solutions from the aspects of production, marketing, and management of Bandeng Rorod partners. The method used was socialization, mentoring, and procurement of machines/tools for production. The programs that have been implemented are in the form of education and socialization of the urgency of IPR protection for MSMEs, Socialization of export strategies for MSMEs, socialization of food security and food labels, procurement of vacuum machines, dough mixers, and stacking steaming pans. With this program, it is hoped that partners will increase the quantity and quality of their products.